Incorporation of sulfonated silica nano particles into polymer blend membrane for PEM fuel cell applications. (16th October 2019) - Joseph Helen Therese, J B Arul; Gayathri, R; Selvakumar, K; Ramesh Prabhu, M; Sivakumar, P
Abstract: In the present work sulfonated poly (ether ether ketone) (SPEEK)/poly (amide imide) (PAI or Torlon) was successfully prepared for various conditions such as percentage compositions of the SPEEK/PAI blended with sulfonated silica (S-SiO2 ). The Nuclear Magnetic Resonance spectroscopy (NMR), Ion Exchange Capacity (IEC) analyses confirm the degree of sulfonation level as 65%. The as-prepared composite membranes were subjected to characterize using Fourier Transform Infrared spectroscopy (FTIR). Surface morphology of the acid-base composite membranes was analyzed by Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM). Other physical properties related to conductivities, ion exchange capacity and proton conductivity were also evaluated for the prepared composite membranes. The 90 wt% SPEEK- 10 wt% PAI- 3 wt% S-SiO2 membrane had (0.75 V) open-circuit voltage (OCV), (350 mA cm −2 ) current density and (120 mW cm −2 ) power density. 90 wt% SPEEK- 10 wt% PAI- 3 wt% S-SiO2 composite showed good proton conductivities, durability and expected for developing of Proton Exchange Membrane Fuel Cell (PEMFC) applications.